2010
DOI: 10.1038/modpathol.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

ERG rearrangement is specific to prostate cancer and does not occur in any other common tumor

Abstract: Background Identification of specific somatic gene alterations is crucial for the insight into the development, progression, and clinical behavior of individual cancer types. The recently discovered recurrent ERG rearrangement in prostate cancer (PCa) might represent a PCa specific alteration that has not been systematically assessed in tumors other than PCa. Aim of this study was to assess, whether the ERG rearrangement and the distinct deletion site between TMPRSS2 and ERG, both predominantly resulting in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 27 publications
7
90
2
Order By: Relevance
“…13 Among these, the most commonly observed and highly PCa-specific event is the promoting linkage of the androgen-regulated gene TMPRSS2 to the oncogenic transcription factor ERG. 18 Other, but rarely observed 5 0 fusions partners of ERG, are SLC45A3 and NDRG1. 2,3 In the vast majority of PCa, ERG rearrangements result in a clonal overexpression of chimeric fusion transcripts encoding truncated variants of the ERG protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Among these, the most commonly observed and highly PCa-specific event is the promoting linkage of the androgen-regulated gene TMPRSS2 to the oncogenic transcription factor ERG. 18 Other, but rarely observed 5 0 fusions partners of ERG, are SLC45A3 and NDRG1. 2,3 In the vast majority of PCa, ERG rearrangements result in a clonal overexpression of chimeric fusion transcripts encoding truncated variants of the ERG protein.…”
Section: Discussionmentioning
confidence: 99%
“…TMA construction was performed as described earlier. 12,18 Briefly, formalinfixed paraffin-embedded PCa tissue blocks were sectioned at 3 mm thick sections, mounted on slides and stained with haematoxylin and eosin. Prior to TMA construction, representative cancer areas were marked by a pathologist (S P).…”
Section: Decalcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Most commonly, fusion of the transcriptional regulator gene ERG (ETSrelated gene) with TMPRSS2 is seen, present in half or more of prostate cancers, although other partner genes, such as ETV1, ETV4 and ETV5, may be involved in translocations. 1,2,7 Subsequent studies have found these gene fusions to appear early in prostate cancer development, 6 present in a subset of cases of prostatic intra-epithelial neoplasia and putative precursor lesions.…”
mentioning
confidence: 99%
“…2,4,12 Although abnormalities of ETS genes are sometimes found in tumors of other organs, ERG-TMPRSS2 fusion is not seen in common neoplasms of other sites, both epithelial and non-epithelial. 3 As such, these abnormalities have begun to demonstrate tremendous potential for broad applications in diagnosis, prognostication and treatment of prostate cancer. 2,5 With regard to therapy, however, gene rearrangements involving transcription factors have unfortunately been largely considered poor targets for pharmacologic therapy, due to their lack of enzymatic activity, location within the nucleus and complex interaction with other proteins required for function.…”
mentioning
confidence: 99%